PENINGKATAN TATA KELOLA ADMINISTRASI BERBASIS GOOGLE DRIVE PADA GERAKAN PEMUDA ANSOR PIMPINAN ANAK CABANG PERAK JOMBANG - Muhammad Mirza Firdaus; Syaiful Makhi Ula Arrois; Abdullah Haq Al Haidary (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2023)
This community service program focuses on mentoring and training for enhancing digital-based administrative skills through the Gerakan Pemuda Ansor (Ansor Youth Movement) at the Sub-Branch Leadership of Perak, Jombang Regency. The decision to conduct this training is based on the upcoming accreditation at each branch, in accordance with the decision letter from the XVIII Grand Conference number 15/KONBES-XVIII/VI/2012 regarding the accreditation of the Gerakan Pemuda Ansor Organization and the upcoming visitation by an assessment team from the Regional Board to the Jombang Branch Leadership. The objectives of this community service are as follows : To assist the officials in enhancing their digital administration skills, to provide new insights into the features of Google Drive as a digital storage medium.to foster collaborations with various stakeholders, especially Ansor's autonomous bodies, to introduce IAI Tribakti to the community, particularly in the Jombang region. The methods employed to achieve these objectives involve lectures and training sessions. Training-related materials are presented through lectures and discussions, followed by practical, hands-on training. The overall outcome of this community service program has been positive and satisfactory.